Reimaging Environmental Education: Urban youths' perceptions and investigations of their communities (Revista Brasileira de Pesquisa em Educação em Ciências, 2014)
In this study we investigate ways that students in an environmental science course connect learning in their communities using photovoice. As a participatory methodology, photovoice provides a means for young people to critically explore issues that impact their everyday environments. Students utilized photovoice and narratives to uncover common themes experienced by young people in their rapidly changing urban neighborhoods. We found that through a photovoice project that incorporated a critical pedagogy of place framework, students were able to critically evaluate the physical spaces that construct their identities while documenting larger global issues that are happening on a local scale including segregation, gentrification, and differential access to spaces and resources. A critical place based pedagogy can challenge dominant ideologies about environmental education by highlighting social justice issues that are happening close to home and most salient to student’s lives.